2003
DOI: 10.1021/la0207365
|View full text |Cite
|
Sign up to set email alerts
|

Optically Tunable Gelled Photonic Crystal Covering Almost the Entire Visible Light Wavelength Region

Abstract: By fixing charged colloidal crystals in a poly(acrylamide) hydrogel matrix, we fabricated photonic crystals whose diffraction peak wavelengths were tunable by applying mechanical stress. The reflection spectrum for a single crystal grain was measured by applying microspectroscopy under compression. The photonic band gap wavelength shifted linearly and reversibly over almost the entire visible light wavelength region (460-810 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 24 publications
(45 reference statements)
0
100
1
2
Order By: Relevance
“…Most polymer materials that exhibit structural color are based on the incorporation of periodically packed colloidal particles into the polymer matrix, or the formation of a porous polymer matrix by etching away the precursor colloidal particles [37][38][39][40][41][42][43][44][45]. These photonic crystalline materials are therefore isotropic in structure, they have poor color quality and weak mechanical response, and their color tuning ability covers narrow wavelength band (< 70 nm).…”
Section: Mechano-responsive Color Tunabilitymentioning
confidence: 99%
“…Most polymer materials that exhibit structural color are based on the incorporation of periodically packed colloidal particles into the polymer matrix, or the formation of a porous polymer matrix by etching away the precursor colloidal particles [37][38][39][40][41][42][43][44][45]. These photonic crystalline materials are therefore isotropic in structure, they have poor color quality and weak mechanical response, and their color tuning ability covers narrow wavelength band (< 70 nm).…”
Section: Mechano-responsive Color Tunabilitymentioning
confidence: 99%
“…The photonic band of a gel-immobilized colloidal crystal is tunable due to an external force. 11,12 An excellent coincidence between the LSP resonance and the photonic band gap is expected due to tuning of the photonic band. We have tried to replace an opal with a gel-immobilized colloidal crystal.…”
mentioning
confidence: 99%
“…As a result, the diffracted wavelength from the colloidal crystal is thermally tunable across the entire visible spectrum. The color of the hydrogel colloidal crystals is also sensitive to pH and ion concentration [78,79], and colloidal crystals embedded in hydrogels can serve as mechanical sensors for measuring strains due to uniaxial stretching or compression [80]. Xia et al reported electrically tunable structural color [81], tunable laser emission [82] and structural color printing [83] using hydrogel colloidal crystals.…”
Section: Crystalline Diffractionmentioning
confidence: 99%